2005
DOI: 10.1128/mcb.25.4.1367-1378.2005
|View full text |Cite
|
Sign up to set email alerts
|

Deltex Regulates T-Cell Activation by Targeted Degradation of Active MEKK1

Abstract: Deltex is known as a Notch signal mediator, but its physiological action mechanism is poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 55 publications
(65 reference statements)
3
48
1
Order By: Relevance
“…At the molecular level, Deltex has been proposed to regulate Notch signals by affecting the transcription of target genes (44,82), altering the intracellular trafficking of Notch receptors (25,26), or participating in a trimolecular complex that targets the Notch receptor for ubiquitin-mediated degradation (54). We identified the Deltex1 gene as a gene that is highly induced by Notch signals in T-cell precursors and demonstrated that expression of Deltex1 mRNA is dynamically modulated during different stages of thymocyte maturation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At the molecular level, Deltex has been proposed to regulate Notch signals by affecting the transcription of target genes (44,82), altering the intracellular trafficking of Notch receptors (25,26), or participating in a trimolecular complex that targets the Notch receptor for ubiquitin-mediated degradation (54). We identified the Deltex1 gene as a gene that is highly induced by Notch signals in T-cell precursors and demonstrated that expression of Deltex1 mRNA is dynamically modulated during different stages of thymocyte maturation.…”
Section: Discussionmentioning
confidence: 97%
“…Although it is well established that Deltex interacts with the intracellular domain of Notch, the mechanism whereby Deltex regulates Notch signals either positively or negatively remains uncertain. Deltex has been proposed to inhibit the transcriptional activation of Notch-responsive genes (31) or to regulate transcription independently of Notch by binding to the transcriptional coactivator p300 (82) or by targeting MEKK1 for degradation (44). Other studies suggest that Deltex regulates the intracellular trafficking of Notch within endosomal compartments (25,26).…”
mentioning
confidence: 99%
“…It is believed that the deactivation of the MAPK pathway is a consequence of negative feedback loops that regulate kinase activity, abundance, and cellular localization through changes in kinase phosphorylation and ubiquitination (28 -31). Degradation of kinases within the MAPK cascade by the ubiquitin-proteasome pathway to attenuate MAPK signaling has been reported for certain MAPKK kinases (MEKK1 and MEKK2) (32,33), MAPKs (ERK2 and ERK7) (34,35), and MAPKKs such as MKK4, which is ubiquitinated by E3 ligase itch (a homologous to the E6-AP carboxyl terminus (HECT) domain-containing Nedd4-like ubiquitin protein ligase) and degraded to negatively regulate JNK activation (31). Whether degradation of MKK6 is involved in deactivation of p38 signaling has not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…5,13 Deltex1 overexpression did not exactly mimic Notch1 suppression by siRNA in HRS cells with respect to unaltered expression of B lineageinappropriate genes, indicating that some of the effects of Notch are Deltex independent. In addition, Deltex1 has other Notchindependent effects, inhibiting MEKK1, a member of the mitogen-activated protein kinase cascade, 39 which might be responsible for the observed differences. Studies are currently underway to identify potential loss of function mutations in the regulatory and coding sequences of the Deltex1 gene in HRS cells.…”
Section: Discussionmentioning
confidence: 99%